Tinjauan Maqashid Syariah terhadap Perlindungan Data Pribadi Nasabah Pada Digital Payment - Ilman Miftahul Fauzi; Fahmi Nurfatwa; Dede San San Ramlan Sandiana; Rimarsha Desta Anjani; Mozza Naiara Fawwaz; Mutia Latifa; Trisna Wijaya (Sekolah Tinggi Agama Islam (STAI) Ki Ageng Pekalongan, Indonesia, 2026)
This study aims to identify the protection of customers’ personal data at digital payments from the perspective of maqashid al-sharia. This qualitative study, conducted as a literature review, utilises data from various academic sources and relevant regulations. The results indicate that, from the perspective of maqashid syariah, personal data can be regarded as an asset that must be safeguarded as a manifestation of hifz mal (protection of property). Consequently, digital service providers bear the responsibility to ensure the security of users’ funds and data as an application of the principle of amanah and the protection of property. This study helps to confirm that the maqashid al-sharia can serve as a formal legal basis for strengthening the security of digital payment services.